Spinal arachnoid diverticula in cats: Clinical presentation, diagnostic imaging findings, treatment, and outcome - João Miguel De Frias; Sofie F. M. Bhatti; George Nye; Rita Gonçalves; Tom Harcourt‐Brown; Angela Fadda; Katia Marioni‐Henry; Hannah Padley; Steven De Decker (Journal of Veterinary Internal Medicine)
Abstract Background Spinal arachnoid diverticulum (SAD) is considered a rare disease in cats. Previous reports mainly classified SAD in cats as acquired. Hypothesis/Objectives The aim of this study was to describe the signalment, clinical presentation, diagnostic imaging findings, and outcome in a group of cats with SAD. Animals Twenty‐one client‐owned cats. Methods Multicenter observational retrospective review of the medical records of cats diagnosed with SAD by magnetic resonance imaging. Results Most cats were Domestic Short Hair (67%), male (63%), and had a wide range of ages (18 weeks to 13 years old). Neuroanatomical localization was consistent with a T3‐L3 myelopathy in 18 cats (86%) and C1‐C5 myelopathy in 3 cats (14%). One cat with a C1‐C5 myelopathy demonstrated bilateral vestibular clinical signs. One cat (5%) had fecal incontinence. Most cats demonstrated a chronic, progressive, nonlateralized, nonpainful myelopathy. No underlying previous or concurrent spinal condition was found in 48% of the cats. No difference in age, body weight, breed, sex, treatment, or outcome was found between cats with or without a concurrent spinal disorder. One cat was euthanized after diagnosis. Six cats improved, 1 deteriorated and 1 remained static after surgery, whereas 3 cats improved, 5 deteriorated and 4 remained static after medical management on the short‐term outcome. Overall, 73% (8/11) of the cats deteriorated on available long‐term follow‐up information. Conclusions and Clinical Importance Spinal arachnoid diverticulum should be considered for cats with chronic, progressive, symmetrical, nonpainful myelopathy, particularly if male and with a history of spinal disease or surgery.